The association between frailty and physical performance in elderly patients with heart failure. (3rd October 2022) - Jin, U; Lee, C J; Yoon, M; Ha, J; Oh, J; Park, S; Lee, S H; Kang, S M
Abstract: Background: Frailty is known to be an important prognostic indicator in heart failure (HF). The Korean version of the frail scale for Koreans (K-FRAIL) has been developed and verified. The purpose of this study is to analyze the relationship between the K-FRAIL scale and physical performance, including muscular fitness and aerobic capacity in patients with HF. Methods: This study included 143 HF patients aged over 65 years from a single tertiary hospital. In these subjects, muscular fitness was assessed using the handgrip test and knee extensor strength measurement, and aerobic capacity was assessed by cardiopulmonary exercise test and 6-minute walk test. Frailty status was measured using the K-FRAIL questionnaire and was classified as robust (K-FRAIL scale: 0), prefrail (1–2), and frail (3–5). Results: Mean age of participants with robust (N=37), prefrail (N=75), and frail (N=31) were 72.5, 73.5, and 76.3 years, respectively. There was no difference in sex and left ventricular ejection fraction (LVEF) among groups, but the estimated glomerular filtration rate (eGFR) was significantly lower as frailty status increased (75.6±17.2 vs. 70.0±20.5 vs. 56.1±23.7 mL/min/1.73 m 2 ; P<0.001). Hand-grip strength and knee extensor muscle strength did not differ among groups. However, peak oxygen consumption (peak VO2; 22.8±5.0 vs. 19.3±4.6 vs. 16.9±4.7 mL/kg/min, P<0.001) and 6-min walk distance (458.4±68.2 vs. 404.5±92.3 vs. 311.2±120.5 m; p<0.001) significantly decreased according to frailty severity. In multivariate regression analysis adjusted for age, sex, haemoglobin, eGFR and LVEF, peak VO2 (β=−0.311; P=0.002) and 6-min walk distance (β=−0.384; P<0.001) showed a significant inverse association with the K-FRAIL scale. With the cut-off value from receiver-operating characteristic curve analysis, peak VO2 (hazard ratio, 5.08; p=0.023) and 6MWT (hazard ratio, 3.99; p=0.020) were independent predictor of frailty according to K-FRAIL scale. Conclusion: In elderly HF patients, physical performance differs according to frailty status, peak VO2 and 6-min walk distance correlates with the K-FRAIL scale better than muscular fitness. Funding Acknowledgement: Type of funding sources: None.